Carbon nanotube / thermoplastic polyurethane composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202611117566.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-27
AI Technical Summary
1.填料分散困难:碳纳米管具有极大的比表面积和表面能,极易发生团聚,难以在聚合物基体中形成均匀的分散体系
1.卓越的分散性与低逾渗阈值:利用甲壳素纳米纤维对碳纳米管进行“隔离包装”,有效防止了碳管的二次团聚,使其在TPU基体中能以较低的添加量构建完善的三维导电网络。
Smart Images

Figure CN122978683A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer functional composite materials technology, and in particular to a carbon nanotube / thermoplastic polyurethane composite material, its preparation method and application. Background Technology
[0002] Thermoplastic polyurethane (TPU) elastomers are widely used in electronics, automotive, and footwear materials due to their excellent abrasion resistance, high elasticity, and processability. With the rapid development of flexible electronics and antistatic technologies, endowing TPU materials with stable electrical conductivity has become a research hotspot. This is typically achieved by adding conductive fillers such as carbon nanotubes (CNTs). However, existing technologies face the following main challenges in preparing conductive TPU composites: 1. Difficulty in dispersing fillers: Carbon nanotubes have extremely large specific surface area and surface energy, making them prone to aggregation and difficult to form a uniform dispersion system in a polymer matrix. This results in the need for high addition amounts to form conductive pathways (high percolation threshold), thereby impairing the mechanical properties of the material.
[0003] 2. Poor interfacial compatibility: The surface of the original carbon nanotubes is chemically inert and lacks active functional groups, resulting in weak interfacial bonding with the polar TPU matrix. Under stress and deformation, the conductive network is easily damaged, leading to unstable electrical properties of the material.
[0004] 3. Limitations of Single Matrix Properties: Polyester-based TPUs have high mechanical strength but poor hydrolysis resistance, while polyether-based TPUs are resistant to low temperatures and hydrolysis and have good resilience but slightly lower strength. Existing technologies often use only one type of TPU, making it difficult to achieve both high strength and resistance to environmental aging.
[0005] Therefore, developing a preparation method that uses bio-based materials to functionalize the surface of conductive fillers and can achieve synergistic performance enhancement by controlling the proportion of TPU matrix has important application value. Summary of the Invention
[0006] To address the aforementioned issues, this invention provides a carbon nanotube / thermoplastic polyurethane composite material, its preparation method, and its application. This method utilizes chitin derivatives to perform "green" coating on carbon nanotubes, solving the dispersion problem, and optimizes the overall performance of the material through blending modification with polyether / polyester TPU.
[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing a carbon nanotube / thermoplastic polyurethane composite material, comprising the following steps: 1) Carbon nanotubes were mixed with ethanol and then subjected to ultrasonic treatment to obtain a carbon nanotube dispersion. 2) The modified material suspension is mixed with the carbon nanotube dispersion obtained in step 1), and then freeze-dried to obtain modified carbon nanotubes; 3) The modified carbon nanotubes described in step 2) are melt-blended with a thermoplastic polyurethane matrix, extruded and granulated, and then molded to obtain a carbon nanotube / thermoplastic polyurethane composite material.
[0008] Preferably, the carbon nanotubes in step 1) include one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carboxylated carbon nanotubes, hydroxylated carbon nanotubes, and aminated carbon nanotubes.
[0009] Preferably, the mass ratio of the carbon nanotubes to the volume ratio of ethanol in step 1) is 1~10g:500mL; The conditions for ultrasonic treatment include: power of 500~800W and time of 60~120min.
[0010] Preferably, the concentration of the modified material in the modified material suspension in step 2) is 0.1~10 mg / mL; The modified material includes one or more of chitin, chitin nanofibers, chitosan, and chitosan nanofibers.
[0011] Preferably, the mass ratio of the modified material suspension to the volume ratio of the carbon nanotube dispersion in step 2) is 0.05~5g:500mL.
[0012] Preferably, the thermoplastic polyurethane matrix in step 3) includes one or more of the following: polyether-type thermoplastic polyurethane matrix, polyester-type thermoplastic polyurethane matrix, polycaprolactone-type thermoplastic polyurethane matrix, and hot melt adhesive-type thermoplastic polyurethane matrix.
[0013] Preferably, the mass ratio of the modified carbon nanotubes to the thermoplastic polyurethane matrix in step 3) is 0.5~20:100.
[0014] Preferably, the molding process in step 3) includes one or more of the following: casting, hot pressing, calendering, injection molding, extrusion molding, coating molding, and dip-load molding; The carbon nanotube / thermoplastic polyurethane composite material is a conductive film, conductive sheet, conductive masterbatch, conductive adhesive film, flexible coating, or composite layered structure.
[0015] The present invention also provides a carbon nanotube / thermoplastic polyurethane composite material prepared by the preparation method described above.
[0016] This invention also provides the application of the carbon nanotube / thermoplastic polyurethane composite material described above in the preparation of artificial skin, robotic skin, flexible pressure sensing layer, wearable electronic bonding layer, flexible electromagnetic shielding layer, antistatic film, electronic workbench mat, flexible battery conductive skeleton, metal negative electrode protective layer, flexible supercapacitor, solar interface evaporator photothermal layer, flexible thermoelectric conversion device light-absorbing and heat-generating layer, flexible photovoltaic module anti-ultraviolet functional layer, antistatic functional layer or weather-resistant protective layer.
[0017] The beneficial effects of this invention are: 1. Excellent dispersibility and low percolation threshold: Chitosan nanofibers are used to "isolate and package" carbon nanotubes, which effectively prevents secondary agglomeration of carbon nanotubes, allowing them to build a complete three-dimensional conductive network in the TPU matrix with a low addition amount.
[0018] 2. Strong interfacial bonding and stability: The abundant amino and hydroxyl groups on the chitin molecular chain can form strong hydrogen bonds or even chemical cross-links with the polar groups in the TPU molecular chain, which greatly improves the interfacial bonding strength of the "filler-matrix" and makes the conductivity of the material stable when bent or stretched.
[0019] 3. Customizable matrix properties: By precisely controlling the ratio of polyether-type and polyester-type TPU, and utilizing their synergistic effect (polyether provides hydrolysis / low-temperature resistance, and polyester provides mechanical strength), the material can meet the stringent requirements of different scenarios, from electronic workbench pads to flexible sensors. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the embodiments will be briefly described below.
[0021] Figure 1 This describes the preparation principle of polyether / polyester hybrid TPU conductive composite materials based on bio-based modified fillers. Detailed Implementation
[0022] This invention provides a method for preparing a carbon nanotube / thermoplastic polyurethane composite material, comprising the following steps: 1) Carbon nanotubes were mixed with ethanol and then subjected to ultrasonic treatment to obtain a carbon nanotube dispersion. 2) The modified material suspension is mixed with the carbon nanotube dispersion obtained in step 1), and then freeze-dried to obtain modified carbon nanotubes; 3) The modified carbon nanotubes described in step 2) are melt-blended with a thermoplastic polyurethane matrix, extruded and granulated, and then molded to obtain a carbon nanotube / thermoplastic polyurethane composite material.
[0023] This invention involves mixing carbon nanotubes with ethanol and then subjecting the mixture to ultrasonic treatment to obtain a carbon nanotube dispersion. Preferably, the carbon nanotubes used in this invention include one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carboxylated carbon nanotubes, hydroxylated carbon nanotubes, and aminated carbon nanotubes. The preferred mass-to-volume ratio of the carbon nanotubes to ethanol is 1-10 g:500 mL. The preferred ultrasonic treatment conditions include a power of 500-800 W and a time of 60-120 min.
[0024] This invention involves mixing a modified material suspension with a carbon nanotube dispersion, followed by freeze-drying to obtain modified carbon nanotubes. In this invention, the concentration of the modified material in the modified material suspension is preferably 0.1~10 mg / mL. In this invention, the modified material preferably includes one or more of chitin, chitin nanofibers, chitosan, and chitosan nanofibers. In this invention, the mass ratio of the modified material suspension to the volume ratio of the carbon nanotube dispersion is preferably 0.05~5 g:500 mL.
[0025] This invention places carbon nanotubes in anhydrous ethanol medium and performs cavitation exfoliation using a self-propelled high-energy ultrasonic processor or ultrasonic disperser. The shear force generated by the ultrasonic cavitation effect breaks the initial aggregation of the carbon nanotubes, resulting in a highly dispersed carbon nanotube dispersion. A pretreated, swollen chitin (or chitin derivative / nanocellulose) nano-suspension is then added to this dispersion. In this system, the nanoscale chitin fibers, due to their large specific surface area, tightly coat the carbon nanotube surface through physical adsorption and chemical bonding. This process introduces a large number of highly reactive functional groups (such as amino-NH2 and hydroxyl-OH) into the carbon nanotube surface in situ. Finally, the modified mixture is freeze-dried to remove the solvent, yielding a fluffy modified carbon nanotube powder.
[0026] This invention involves melt blending, extrusion granulation, and molding of modified carbon nanotubes with a thermoplastic polyurethane matrix to obtain a carbon nanotube / thermoplastic polyurethane composite material. In this invention, the thermoplastic polyurethane matrix preferably includes one or more of polyether-type thermoplastic polyurethane matrix, polyester-type thermoplastic polyurethane matrix, polycaprolactone-type thermoplastic polyurethane matrix, and hot melt adhesive-type thermoplastic polyurethane matrix. In this invention, the mass ratio of modified carbon nanotubes to thermoplastic polyurethane matrix is preferably 0.5~20:100. In this invention, the molding process preferably includes one or more of casting, hot pressing, calendering, injection molding, extrusion molding, coating molding, and impregnation loading molding. In this invention, the carbon nanotube / thermoplastic polyurethane composite material is preferably a conductive film, conductive sheet, conductive masterbatch, conductive adhesive film, flexible coating, or composite layered structure.
[0027] Choose one of the following two matrix formulations based on the application scenario requirements: 1. Type A (Blended): Polyether-type TPU and polyester-type TPU are physically blended at a mass ratio of (10:90) to 1 (90:10). The preferred ratio is 70 parts of polyether-type TPU and 30 parts of polyester-type TPU to obtain the best balance between toughness and strength.
[0028] 2. Type B (Single Type): Uses only polyether-type TPU or only polyester-type TPU as the matrix.
[0029] Step 3: Melt Blending and Molding The modified carbon nanotube powder obtained in step one is mixed evenly with the TPU matrix particles selected in step two, and then added to a twin-screw extruder for melt blending and extrusion. After granulation, conductive masterbatch is obtained. Finally, conductive TPU film, sheet or product is obtained by high-temperature plasticizing and molding through a casting machine or injection molding machine.
[0030] The present invention also provides a carbon nanotube / thermoplastic polyurethane composite material prepared by the preparation method described above.
[0031] This invention also provides the application of the carbon nanotube / thermoplastic polyurethane composite material described above in the preparation of artificial skin, robotic skin, flexible pressure sensing layer, wearable electronic bonding layer, flexible electromagnetic shielding layer, antistatic film, electronic workbench mat, flexible battery conductive skeleton, metal negative electrode protective layer, flexible supercapacitor, solar interface evaporator photothermal layer, flexible thermoelectric conversion device light-absorbing and heat-generating layer, flexible photovoltaic module anti-ultraviolet functional layer, antistatic functional layer or weather-resistant protective layer.
[0032] To further illustrate the present invention, the following detailed description is provided in conjunction with embodiments, but these should not be construed as limiting the scope of protection of the present invention.
[0033] Example 1 Preparation of carbon nanotube / polycaprolactone (TPU) composite conductive film: 1. Filler Modification: 10 g of multi-walled carbon nanotubes (XFM03) were added to 500 mL of anhydrous ethanol and treated with an 800 W ultrasonic cell disruptor for 60 minutes until the solution became a uniform black slurry. Then, 2 g of chitosan (Maclean C850347) was added to prepare a 10 mg / mL suspension, and ultrasonic dispersion was continued for 30 minutes. The mixture was freeze-dried for 24 hours to obtain chitosan-coated modified carbon nanotube powder.
[0034] 2. Matrix Formulation: 1000 g of polycaprolactone-type TPU (Wanhua polycaprolactone 1565) was selected as the matrix material and vacuum-dried at 80 ℃ for 6 hours to remove moisture from the matrix particles. Polycaprolactone-type TPU possesses good flexibility, mechanical strength, and hydrolytic stability, making it suitable for use as a flexible artificial skin material in long-term contact with sweat, humid air, or the human body surface.
[0035] 3. Co-extrusion: Add the modified carbon nanotube powder to polycaprolactone-type TPU particles at 3% to 8% of the total matrix mass and premix in a high-speed mixer.
[0036] 4. Molding: Pour the mixture into a twin-screw extruder, set the temperature range to 150℃-180℃, and the rotation speed to 100~250 rpm for extrusion granulation. Finally, feed the particles into a casting machine, extrude and cast at 175℃, and rapidly cool them through cooling rollers to obtain a conductive TPU film with a thickness of 0.1 mm.
[0037] The resulting composite film exhibits good flexibility, electrical conductivity stability, and resistance to damp heat, maintaining relatively stable electrical conductivity under bending, stretching, or compression. This material can be used as artificial skin, robotic skin, flexible pressure sensing layers, wearable electronic bonding layers, or human motion monitoring sensing layers.
[0038] Example 2 Preparation of flexible electromagnetic shielding film composed of carbon nanotubes / TPU: 1. Filler modification: Chitosan derivative-coated modified carbon nanotube powder was prepared according to the method in Example 1.
[0039] 2. Matrix Formulation: Select 700 g of polyether-type TPU (Wanhua 8185RV) with a hardness of 85 A and 300 g of polyester-type TPU (Wanhua polycaprolactone 1185EC) with a hardness of 85 A, and mix them evenly. This 7:3 ratio aims to combine the low-temperature hydrolysis resistance of the polyether type with the high mechanical strength of the polyester type.
[0040] 3. Co-extrusion: The modified carbon nanotube powder (added at 5% of the total mass of the matrix) is pre-mixed with the well-mixed TPU matrix in a high-speed mixer.
[0041] 4. Molding: The mixture is poured into a twin-screw extruder, the temperature range is set to 170 ℃-190 ℃, the speed is 200 rpm, and the extrusion is granulated. Finally, the particles are fed into a casting machine, extruded and cast at 175 ℃, and then rapidly cooled by cooling rollers to obtain a conductive TPU film with a thickness of 0.1 mm.
[0042] In this composite film, modified carbon nanotubes construct a continuous conductive network within the TPU matrix, thereby achieving excellent electromagnetic shielding performance. This meets the future needs of flexible electronics for anti-interference and lightweight protection, and can be used for electromagnetic interference protection in flexible circuits, smart textiles, robotic skin, and portable electronic devices.
[0043] Example 3 Preparation of conductive framework and metal anode protective layer for carbon nanotube / TPU composite flexible battery: 1. Filler modification: Chitosan derivative-coated modified carbon nanotube powder was prepared according to the method in Example 1.
[0044] 2. Matrix formulation: In this embodiment, the TPU matrix is Wanhua polycaprolactone 1180.
[0045] 3. Preparation: Modified filler (3%~8%) is premixed with TPU matrix in a high-speed mixer at a temperature range of 150℃-180℃ and a rotation speed of 100~250 rpm, and then extruded and granulated. Finally, the particles are fed into a casting machine and extruded and cast at 175℃, and then rapidly cooled by cooling rollers to obtain a conductive TPU film. The obtained composite film or its dispersion coating can be attached or coated onto the surface of metal anodes such as zinc and lithium, and can be used as a flexible modified protective layer. The amino and hydroxyl groups in the chitosan derivative can interact with ions, which helps to regulate the ion flux distribution; the carbon nanotube conductive network can improve the uniformity of interfacial electron transport, thereby reducing the risk of local current density concentration and uneven dendrite growth.
[0046] This composite material can alleviate problems such as electrode cracking, interface peeling, and conductive network failure in flexible batteries during bending, compression, or long-cycle processes. It is suitable for flexible zinc and lithium batteries, flexible supercapacitors, and wearable energy storage devices.
[0047] Example 4 Preparation of flexible solar thermal utilization materials composed of carbon nanotubes / TPU composites: 1. Filler modification: Chitosan derivative-coated modified carbon nanotube powder was prepared according to the method in Example 1.
[0048] 2. Matrix preparation: In this embodiment, Wanhua 8170RV was selected as the TPU matrix and vacuum dried at 80 °C for 6 hours to remove moisture from the matrix particles.
[0049] 3. Preparation: Mix the modified filler (3%~8%) with the TPU matrix evenly, and prepare the resulting composite masterbatch into an 8% DMF solution. It can be formed by casting, coating or impregnation of porous substrates. Dry at 120℃ for 24 hours to evaporate the solvent and obtain a film, adhesive film or composite sheet.
[0050] This composite material can be used as a UV-resistant, weather-resistant, or antistatic encapsulation layer in flexible photovoltaic devices. The TPU matrix provides flexibility, transparency, and barrier protection, while carbon nanotubes help improve resistance to UV aging, thereby improving the environmental stability and lifespan of flexible photovoltaic modules. It can also be used as a photothermal layer in solar interface evaporators, utilizing the porous water transport channels of chitosan and the photothermal effect of carbon nanotubes to achieve efficient seawater desalination and wastewater treatment. Furthermore, it can be used as a flexible thermoelectric conversion device, utilizing the photothermal temperature difference to achieve all-weather clean energy collection.
[0051] Example 5 Preparation of hot melt adhesive type TPU conductive composite material: 1. Filler Modification: 10 g of multi-walled carbon nanotubes (XFM02) were added to 500 mL of anhydrous ethanol and treated with an ultrasonic cell disruptor at 500 W for 120 minutes to obtain a uniform carbon nanotube dispersion. Subsequently, 2 g of chitosan (Maclean C708815) was added to prepare a 5 mg / mL suspension, and ultrasonic dispersion was continued for 30 minutes. The resulting mixed dispersion was freeze-dried for 24 hours to obtain chitosan-coated modified carbon nanotube powder.
[0052] 2. Matrix preparation: 1000 g of Wanhua transparent hot melt adhesive TPU masterbatch was selected as the matrix material and vacuum dried at 50 ℃~60 ℃ for 4 hours to remove the adsorbed moisture on the surface and inside of the masterbatch.
[0053] 3. Preparation: Modified filler (3%~8%) and TPU matrix are melt-blended according to the method in Example 1, except that the processing temperature is controlled at 70 ℃~120 ℃.
[0054] This material can be melt-blended and molded at relatively low processing temperatures, reducing the thermal impact of high-temperature processing on the chitosan coating and TPU matrix. The resulting composite material combines hot-melt bonding properties, flexibility, and electrical conductivity, making it suitable for conductive hot-melt adhesive films, flexible electronic bonding layers, antistatic composite films, and adhesive layers for wearable devices.
[0055] Example 6 TPU material for antistatic electronic workbench mats: 1. Filler modification: Chitosan derivative-coated modified carbon nanotube powder was prepared according to the method in Example 1.
[0056] 2. Matrix formulation: 1000 g of polyether-type TPU (Wanhua 8185RV) was selected separately to meet the strict requirements of the electronics industry for materials with hydrolysis resistance and anti-aging properties.
[0057] 3. Preparation: Modified filler (3%~8%) is melt-blended with TPU matrix according to the method in Example 1. The resulting composite granules are vacuum-dried at 80 °C for 6~8 h to remove moisture. Injection molding is performed under conditions of barrel temperature 170~190 °C, pressure 60~100 MPa, and mold temperature 30~50 °C. After pressure holding, cooling and shaping, and demolding, the sheet is obtained.
[0058] This material has excellent antistatic properties and no exudates on its surface (compared to traditional methods that add small molecule antistatic agents). It has a long service life and is very suitable for use as a workbench mat for precision electronic assembly. It can also be used to repair the skin function of robots and the surface of devices.
[0059] Example 7 Preparation of high-toughness, hydrolysis-resistant conductive TPU film: 1. Filler modification: Chitosan derivative-coated modified carbon nanotube powder was prepared according to the method in Example 5.
[0060] 2. Matrix preparation: In this embodiment, polyether-type TPU (Wanhua 8185RV) and polyester-type TPU (Wanhua 1185EC) are mixed at a mass ratio of 7:3.
[0061] 3. Preparation: Modified filler (3%~6%) and TPU matrix are premixed in a high-speed mixer, then poured into a twin-screw extruder. The temperature range is set to 150℃-180℃ and the speed is 150 rpm for extrusion granulation. Finally, the particles are fed into a casting machine and extruded and cast at 160℃. After rapid cooling by cooling rollers, a conductive TPU film with a thickness of 0.2 mm is obtained.
[0062] Test results: The surface resistivity of the thin film remained stable at 10. 4 With a tensile strength at the Ω / sq level, it is 20% higher than the unmodified filler sample, and the resistance change rate is less than 5% after multiple bends, demonstrating excellent flexibility and electrical conductivity stability.
[0063] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a carbon nanotube / thermoplastic polyurethane composite material, characterized in that, Includes the following steps: 1) Carbon nanotubes were mixed with ethanol and then subjected to ultrasonic treatment to obtain a carbon nanotube dispersion. 2) The modified material suspension is mixed with the carbon nanotube dispersion obtained in step 1), and then freeze-dried to obtain modified carbon nanotubes; 3) The modified carbon nanotubes described in step 2) are melt-blended with a thermoplastic polyurethane matrix, extruded and granulated, and then molded to obtain a carbon nanotube / thermoplastic polyurethane composite material.
2. The preparation method according to claim 1, characterized in that, Step 1) The carbon nanotubes include one or more of single-walled carbon nanotubes, multi-walled carbon nanotubes, carboxylated carbon nanotubes, hydroxylated carbon nanotubes, and aminated carbon nanotubes.
3. The preparation method according to claim 1, characterized in that, Step 1) The mass ratio of the carbon nanotubes to the volume ratio of ethanol is 1~10g:500mL; The conditions for ultrasonic treatment include: power of 500~800W and time of 60~120min.
4. The preparation method according to claim 1, characterized in that, Step 2) The concentration of the modified material in the modified material suspension is 0.1~10 mg / mL; The modified material includes one or more of chitin, chitin nanofibers, chitosan, and chitosan nanofibers.
5. The preparation method according to claim 1, characterized in that, Step 2) The mass ratio of the modified material suspension to the volume ratio of the carbon nanotube dispersion is 0.05~5g:500mL.
6. The preparation method according to claim 1, characterized in that, Step 3) The thermoplastic polyurethane matrix includes one or more of the following: polyether-type thermoplastic polyurethane matrix, polyester-type thermoplastic polyurethane matrix, polycaprolactone-type thermoplastic polyurethane matrix, and hot melt adhesive-type thermoplastic polyurethane matrix.
7. The preparation method according to claim 1, characterized in that, Step 3) The mass ratio of the modified carbon nanotubes to the thermoplastic polyurethane matrix is 0.5~20:
100.
8. The preparation method according to claim 1, characterized in that, Step 3) The molding process includes one or more of the following: casting, hot pressing, calendering, injection molding, extrusion molding, coating molding, and dip-load molding; The carbon nanotube / thermoplastic polyurethane composite material is a conductive film, conductive sheet, conductive masterbatch, conductive adhesive film, flexible coating, or composite layered structure.
9. A carbon nanotube / thermoplastic polyurethane composite material prepared by the preparation method according to any one of claims 1 to 8.
10. The application of the carbon nanotube / thermoplastic polyurethane composite material of claim 9 in the preparation of artificial skin, robotic skin, flexible pressure sensing layer, wearable electronic bonding layer, flexible electromagnetic shielding layer, antistatic film, electronic workbench mat, flexible battery conductive skeleton, metal negative electrode protective layer, flexible supercapacitor, solar interface evaporator photothermal layer, flexible thermoelectric conversion device light-absorbing and heat-generating layer, flexible photovoltaic module anti-ultraviolet functional layer, antistatic functional layer or weather-resistant protective layer.